Traveling, Rolling, and Smoking: The History of the Union Cigar Makers in the United States - Jordan, Joshua (My University, 2009)
This paper examines the cigar making industry in the United States from its rise in the second half of the 19th Century, to its decline in the early part of the 20th Century, more specifically from about 1880 to 1920. It focuses on this industry mainly through the Cigar Makers' International Union. The scope of this labor union is narrowed to Local 162 of Green Bay, WI. This paper briefly covers the beginnings of the labor movement and tobacco growing in Wisconsin. The argument is that the CMIU's programs and connections with other labor unions benefitted its members including immigrants and women. This is supported by evidence from records from Local 162, as well as US Census Data.
Keywords: Cigar Makers' International Union of America; Cigar Makers' International Union of America. Local 162 (Green Bay, Wis.); Cigar industry--United States--History; Cigar industry--Wisconsin--Green Bay--History; Labor unions--Wisconsin--Green Bay--History; Labor movement--Wisconsin--History; Tobacco--Wisconsin--History